Electrochemical Glucose Oxidation Using Glassy Carbon Electrodes Modified with Au-Ag Nanoparticles: Influence of Ag Content - García Morales, Nancy Gabriela; García Cerda, Luis Alfonso; Puente Urbina, Bertha Alicia; Blanco Jerez, Leonor María; Antaño López, René; Castañeda Zaldivar, Federico (2015)
This paper describes the application of glassy carbon modified electrodes bearing Aux-Agy nanoparticles to catalyze the electrochemical oxidation of glucose. In particular, the paper shows the influence of the Ag content on this oxidation process. A simple method was applied to prepare the nanoparticles, which were characterized by transmission electron microscopy, Ultraviolet-Visible spectroscopy, X-ray diffraction spectroscopy, and cyclic voltammetry. These nanoparticles were used to modify glassy carbon electrodes. The effectiveness of these electrodes for electrochemical glucose oxidation was evaluated. The modified glassy carbon electrodes are highly sensitive to glucose oxidation in alkaline media, which could be attributed to the presence of Aux-Agy nanoparticles on the electrode surface. The voltammetric results suggest that the glucose oxidation speed is controlled by the glucose diffusion to the electrode surface. These results also show that the catalytic activity of the electrodes depends on the Ag content of the nanoparticles. Best results were obtained for the Au80-Ag20 nanoparticles modified electrode. This electrode could be used for Gluconic acid (GA) production.